Histoarchitecture of the Ovary of Rhipicephalus (Boophilus) annulatus during Pre- and Postengorgement Period - Sreelekha Kanapadinchareveetil; Leena Chandrasekhar; Jyothimol Gopi; Dibya Ranjan Lenka; Aswathi Vasu; Ajith Kumar KGopalan; Suresh N. Nair; Reghu Ravindran; Sanis Juliet; Srikanta Ghosh (The Scientific World Journal)
The present communication describes the detailed day wise study of histological changes of the ovary of Rhipicephalus (Boophilus) annulatus in the postengorgement period together with the systematic classification of their oocytes. The ovary of R. (B.) annulatus is panoistic type with an asynchronous development of oocytes. All the stages (II, III, IV, and V) of oocytes except stage I were similar to R. (B.) microplus. The stage I oocytes showed basophilia, which was not reported earlier in other species of ticks. Day wise changes were in the form of presence of oogonia in partially fed and day one engorged adults, considerable degeneration of oocytes on day two, emergence of new wave of oocytes on day three, presence of mature oocytes up to day eight, and complete degeneration of ovarian tissue from day eight onwards. The degenerative changes in the ovary appeared initially in the oocytes followed by germinal epithelium.